Meaning Variations of QÄla (Ù‚Ø§Ù„) in Indonesian Language - Nikmah, Khoirin (Arabic Education Department, Islamic Studies Faculty, University Muhammadiyah of Malang, 2019)
One of main component for every language is verb. In Arabic, q?la (???) is one of verbs which substantively is used in many oral and written language due to its wide meaning. This research focuses on meaning variation of q?la (???) when it was translated into Indonesian. In this study, differential meaning can be caused by differential speaker and also differential context. Thereby, the research aims to classify and explain every single meaning of q?la (???) verb. This descriptive qualitative research uses observation method with tapping technique. Meanwhile, the data was analyzed by translational method, referential method, and pragmatics method. The result of the research shows that; (1) There are three differential meanings of q?la (???) according to speaker perspective, as well as ?berfirman?, ?bersabda?, and ?berkata?. (2) There are some differential meanings of q?la (???) according to linguistics perspective, such as ?berkata, mengatakan, mengabarkan, mengumumkan, berbicara, mengucapkan, mengaku, pendapat, bertanya, menjawab, perintah, and berdoa.